Resposta:
Explicação passo a passo:
a)
ay + ax ==> fator comum
a*( y + x)
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
b)
4x² - 16 ==> diferença de dois quadrados
(2x + 4)*( 2x - 4)
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
c)
x² + x ==> fator comum
x*( x + 1)
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
d)
x³y³ + 4x²y²==> fator comum
x²y²*( xy + 4)
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
e)
a² + 2ab + b²=> trinômio do quadrado perfeito
(a + b)²
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
f)
4x²-16xy+16y²=>trinômio do quadrado perfeito
(2x - 4y)²
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
g)
xy + 2x - 2a + 2b=> fator comum
x*( y + 2) - 2*(a + b)
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
h)
25x⁴- y⁶=> diferença de dois quadrados
( 5x²+ y³)*(5x² - y³)